Higher-derivative theory of (2+1)-dimensional gravity - Accioly, A.; Azeredo, A.; Mukai, H. (Elsevier B.V., 2001)
Higher-derivative gravity in 2 + 1 dimensions is considered. The general solution of the linearized field equations in a three-dimensional version of the Teyssandier gauge is obtained, and from that the solution for a static pointlike source is found. The deflection of light rays is also analysed. (C) 2001 Elsevier B.V. B.V. All rights reserved.